Mind mapping for dummies - Rustler, Florian (John Wiley & Sons, 2012)
Mind mapping is a structured visualisation technique that can improve all areas of your personal and professional life. Rustler explains how mind mapping works, and walks you through proven techniques for everything from project management to maximising creativity.
Keywords: Mind maps; Problem solving -- Graphic methods; Decision making -- Graphic methods; Creative ability -- Problems, exercises, etc; Success in business; Creative ability; Imagination; Memory; Perception; Problem solving; Creativity; Problem Solving; Résolution de problème; Méthodes graphiques; Prise de décision; Méthodes graphiques; Créativité; Problèmes et exercices; Succès dans les affaires; Créativité; Mémoire; Résolution de problème; creativity; imagination; memory (psychological concept); SELF-HELP; Personal Growth; Memory Improvement; Développement d'aptitudes; Psychologie; Cerveau; Sciences cognitives; Méthodologie; Organisation du travail; Autoformation; Decision making; Graphic methods; Problem solving; Graphic methods; Problems and exercises